No Association Between Thrombus Perviousness and Cardioembolic Stroke Etiology in Basilar Artery Occlusion Stroke - Kufner, Anna; Endres, Matthias; Scheel, Michael; Leithner, Christoph; Nolte, Christian H.; Schlemm, Ludwig (Frontiers in Neurology, 2021)
Background: Thrombus perviousness (TP) quantified by thrombus attenuation increase (TAI) assessed on acute non-contrast computed tomography (NCCT) and CT angiography (CTA) may be associated with stroke etiology in anterior circulation ischemic stroke. We investigated whether TP is associated with stroke etiology and recanalization after mechanical thrombectomy in patients with acute basilar artery occlusion (BAO). Methods: Eighty patients with complete BAO and in-house acute imaging from a prospectively maintained database were included. Two raters independently segmented the complete thrombus on co-registered NCCT and CTA to determine TAI in Hounsfield units (HUCTA–HUNCCT); averaged values of the raters were used for analysis. Recanalization to modified treatment in cerebral ischemia (mTICI) score 2b/3 was considered successful, and 90-day modified Rankin Scale score 0–2 was considered favorable. Results: TAI did not differ between patients with different stroke etiologies; median TAI in patients with cardioembolic stroke (n = 36) was −0.47 (interquartile range −4.08 to 7.72), 1.94 (−8.14 to 10.75) in patients with large artery atherosclerosis (LAA; n = 25), and −0.99 (−6.49 to 5.40) in patients with stroke of undetermined origin (n = 17; p = 0.955). Binary logistic regression analyses did not identify TAI as an independent indicator of cardioembolic stroke (adjusted odds ratio [OR] vs. LAA stroke: 1.0 [95% CI: 0.95–1.0], p = 0.751). There was no association with successful recanalization (adjusted OR 1.4 [0.70–2.7], p = 0.345) or favorable outcome (adjusted OR 1.1 [95% CI: 0.94–1.2], p = 0.304). Conclusion: In contrast to proximal middle cerebral artery occlusions, TP in BAO patients is not associated with cardioembolic stroke etiology. Larger confirmatory studies to establish the potential role of TP for clinical applications should focus on patients with anterior circulation stroke.